Hedonische Preisindizes für Transaktionen von Wohneigentum - dargestellt am Beispiel der Stadt Karlsruhe. Ein Beitrag zur Bereitstellung von Zeitreihen für die Marktwertermittlung und Marktprognose - Michl, Peter (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft / Hrsg.: Karlsruher Institut für Technologie, Lehrstuhl, 2018)
This work addresses the lack of availability of regional hedonic housing price indices as the basis for market analysis and valuation in Germany. Based on data from the valuation expert committee of Karlsruhe, an analysis of the feasibility and estimation of price indices for submarkets of residential property follows. Recommendations regarding the methodology as well as the improvement of the data collection und the data quality are transferable to other valuation expert committees.